2014
DOI: 10.1158/0008-5472.can-14-1212
|View full text |Cite
|
Sign up to set email alerts
|

Densely Ionizing Radiation Acts via the Microenvironment to Promote Aggressive Trp53-Null Mammary Carcinomas

Abstract: Densely ionizing radiation, which is present in the space radiation environment and used in radiation oncology, has potentially greater carcinogenic effect compared with sparsely ionizing radiation that is prevalent on earth. Here, we used a radiation chimera in which mice were exposed to densely ionizing 350 MeV/amu Si-particles, g-radiation, or sham-irradiated and transplanted 3 days later with syngeneic Trp53-null mammary fragments. Trp53-null tumors arising in mice irradiated with Si-particles had a shorte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Recent studies are making efforts to develop appropriate mouse models of human risk using genetically engineered mice and other techniques [ 40 , 41 , 44 ], however they have not been used to estimate RBE values at this time. An important source of data on values of RBE or RBE max for high LET radiation is tumor induction and life-shortening studies in mice or rats with HZE particles or fission neutrons (reviewed in [ 45 , 46 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies are making efforts to develop appropriate mouse models of human risk using genetically engineered mice and other techniques [ 40 , 41 , 44 ], however they have not been used to estimate RBE values at this time. An important source of data on values of RBE or RBE max for high LET radiation is tumor induction and life-shortening studies in mice or rats with HZE particles or fission neutrons (reviewed in [ 45 , 46 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports [ 25 , 28 , 39 41 , 44 ] have suggested that HZE particles and neutrons could produce more lethal tumors compared to tumors produced by low LET radiation or background tumors, which is a qualitative difference not accounted for in current risk estimates. For low LET radiation there is an implicit assumption made by epidemiology models that the tumors induced by radiation are similar to background tumors in a population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports (Fry et al, 1985;Alpen et al, 1993;Dicello et al, 2004;Weil et al, 2009Weil et al, , 2014Grahn et al, 1992;Imaoka et al, 2007;Trani et al, 2010;Datta et al, 2013;Illa-Bochaca et al, 2014;Wang et al, 2015) have suggested that HZE particles and neutrons could produce more lethal tumors compared to tumors produced by low LET radiation or background tumors, which is a qualitative difference not accounted for in current risk estimates. Table 3 summarizes these findings from animal studies with HZE particle beams.…”
Section: Tumor Modelmentioning
confidence: 95%
“…Mammary tumors in SD rats (Imaoka et al, 2007) or transgenic mice (Illa-Bochaca et al, 2014) Differences in mammary tumor types comparing heavy ions to low LET radiation with more aggressive tumors observed.…”
Section: Tumor Modelmentioning
confidence: 99%